Zika Virus (ZIKV): A New Emerging Pathogen Transmitted by Aedes Mosquitoes (Diptera: Culicidae) in the Latin American Subcontinent - Calderón Arguedas, Ólger (2016)
Aedes aegypti and Aedes albopictus (Diptera: Culicidae) are two species of synanthropic mosquitoes that are common in outdoor and indoor domiciliary environments in tropical countries. Their vectorial competence and vectorial capacity make them excellent biological vectors for the main arboviruses that affect human beings. Both Aedes species are listed as the primary vectors of dengue (DENV) and chikungunya (CHIKV) viruses, which circulate in many American countries. The recent introduction of Zika virus (ZIKV) into the Latin American subcontinent and its association with microcephaly and Guillain-Barre syndrome has alerted health authorities about the sanitary emergency that the presence of this new virus in the American territory represents. The emergence of this pathogen raises the necessity to improve the epidemiologic and entomologic surveillance systems and to develop new strategies of prevention and control. This review aims to provide an overview of ZIKV and the role of Ae. aegypti and Ae. albopictus in its transmission.